Biotechnological potential of microalgae: storage methods and non-cryogenic factors of cryopreservation efficiency - Chernobai, Nadiia; Gerilovych, Anton; Shevchenko, Nadiia (Problems of Cryobiology and Cryomedicine, 2025)
The review considers the prospects for the use and preservation techniques for microalgal collection samples. Microalgae have significant biotechnological potential in the food, pharmaceutical, environmental and energy sectors. The paper analyzes and summarizes current methods of maintaining microalgae cultures with a focus on their stability, preservation of biological properties, and long-term storage capabilities. The work includes a comparison of different approaches to microalgae preservation, including batch subcultivation, lyophilization, and cryopreservation. Particular attention is paid to cryopreservation as an effective method of long-term storage of genetically stable cultures, which minimizes the risk of losing valuable biotechnological characteristics. The influence of the stage of culture development, cell concentration in the suspension, cold adaptation, and centrifugation on the survival of microalgae after cryopreservation was determined. The results obtained are important for the development of biotechnological and environmental programs related to the use of microalgae. Probl Cryobiol Cryomed 2025; 35(2):57–67